The Presynaptic v-ATPase Reversibly Disassembles and Thereby Modulates Exocytosis but Is Not Part of the Fusion Machinery - Anna Bodzęta; Martin Kahms; Jürgen Klingauf (Cell Reports, 2017)
Vacuolar H+-ATPase (v-ATPase) is a multi-subunit complex comprising two domains: the cytosolic V1 domain catalyzing ATP hydrolysis and the membranous V0 sector translocating protons across membranes. In addition to proton pumping, a direct function of the V0 proteolipid ring in membrane fusion has been proposed for yeast vacuolar fusion and synaptic vesicle exocytosis in Drosophila. Here, we show in cultured hippocampal neurons that in recycling synaptic vesicles, v-ATPases are only transiently assembled in a pH-dependent fashion during the tightly coupled cycle of exo-endocytosis. Upon locking v-ATPase in an assembled state by saliphenylhalamide, we observed use- and time-dependent release depression for stimuli exceeding release of primed vesicles but no abrogation of exocytosis. Thus, the membranous V0 sector is not part of the exocytotic fusion machinery. Instead, v-ATPase modulates release upstream of docking to favor fusion of fully filled synaptic vesicles.